Verifikasi Metode Uji Arsen dalam Contoh Mainan Anak dengan Spektrofotometer Serapan Atom Generator Uap Hidrida (Method Verification of Assay Arsenic in Toy Sample with Absorption Atomic Spectrophotometer Hydrid Vapor Generator) - Fahrizal Hazra; Susanti Pratiwi Purnama; Suri Mulyani Sari (IPB University, 2014)
The safety of toys as one of important factors needs to be considered. It can be seen from the presence of heavy metals such as arsenic (As). The analysis of heavy metal arsenic in children's toys can use the verified SNI ISO 8124-3 : 2010 method. Verification activities are needed to verify that the laboratory is able to perform a test which is using such method, and the result are valid. Parameters used in this verification were linearity, limit of detection (LOD), limit of quantitation (LOQ), precision, and accuracy. Based on the verification result of Assay Arsenic in toys with Atomic Absorption Spectrophotometer Hydrid Vapor Generator (HVG), good liearity had a correlation coefficient (r) of 0.9993. The limit of detectin (LOD) and limit of quantitation (LOQ) obtained was 0.0113 mg/Kg and of 3.39%. The accuracy had a recovery value 97.66%. The experimental results showed that the Assay Arsenic in toys with Atomic Absorption Spectrophotometer Hydrid Vapor Generator (HVG) can be used as routine analysis.Keywords : arsenic, atomic absorption spectrophotometer, hydrid vapor generator, verification